Gamma aminobutyric acid (GABA) production in Escherichia coli with pyridoxal kinase (pdxY) based regeneration system - Ham, Sion; Bhatia, Shashi Kant; Gurav, Ranjit; Choi, Yong Keun; Jeon, Jong Min; Yoon, Jeong Jun; Choi, Kwon Young; Ahn, Jungoh; Kim, Hee Taek; Yang, Yung Hun (Enzyme and Microbial Technology, 2022)
Gamma-aminobutyric acid (GABA) is a non-proteinogenic amino acid act as a major neurotransmitter inhibitor in the nervous system of mammals. It also used as a precursor of bioplastics synthesis such as N-methylpyrolidone and polyamide 4. Chemical-based synthesis methods have many environmental-related issues, so efforts have been made to develop biosynthetic methods to produce GABA. Glutamate decarboxylase (GAD) transforms L-glutamate to GABA using pyridoxal 5′-phosphate (PLP) as a cofactor. Bioconversion of GABA with whole cells overexpressing the glutamate decarboxylase has advantages of fewer byproducts and rapid reaction. However, there is a bottleneck in the whole-cell bioconversion system i.e., higher GABA production require a large amount of cofactor PLP which make the process costly. Therefore, pyridoxal kinase (PdxY) able to regenerate PLP was introduced in the whole-cell system to construct a new GABA producing system. Culture and reaction conditions were optimized, and 100% conversion of 0.6 M MSG was obtained. This study reports that a competitive level of GABA production could be achieved without supplying additional PLPs.
Keywords: Acid production; Cofactors; Gamma-aminobutyric acids; Glutamate decarboxylase; Pyridoxal 5′-phosphate; Pyridoxal kinase; Regeneration system; Whole cell; Whole-cell bioconversion; γ-Aminobutyric acid; Escherichia coli; gamma-Aminobutyric Acid; Glutamate Decarboxylase; Pyridoxal Kinase; Pyridoxal Phosphate; Glutamate decarboxylase; Pyridoxal 5′-phosphate; Pyridoxal kinase; Whole-cell bioconversion; γ-Aminobutyric acid